قرض اور بیع سے متعلقہ کرنسی کے مسائل اور شرعی احکام :فقہاء کی آراء کا تجزیاتی مطالعہ: A comprehensive study of the currency-related issues and Shariah rulings concerning loans and sales involves analysing the perspectives of jurists (fuqaha) - USMAN, HAFIZ MUHAMMAD; Hussain, Aqsa; Rasheed, Rasheed (AL-IDRAK JOURNAL, 2023)
There is no doubt that Islam is a universal constitution; it is a religion that corresponds to the circumstances and requirements of all times, and the phrase includes the commandments of the sphere of life. There are instructions in Islam regarding the sphere of life. In human society, the status of "money" for mutual transactions is like that of a backbone; instead, it is the backbone of mutual affairs. This paper is about Zakat and trade issues regarding Currency. Zakat is payable on strong debts, i.e. money that is owed to you that you are confident will be paid. This may include personal loans to friends and family. This does not include outstanding wages, dowry, inheritance or assets held in trust (other than assets held under a Bare Trust). Trading is not haram, provided that there is 1) no interest element, 2) trades are conducted “hand to hand”, and 3) the stocks, commodities, or currencies purchased do not offend against the tenets of Islam. With the emergence of modern forms of currency, new problems are arising in terms of currency. The important need of the present age is to bring forward the opinions of contemporary jurists regarding these problems and their interpretation in the light of the Qur'an, Sunnah and Islam.